2019
DOI: 10.1128/aac.00730-19
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Based Efflux Pump Inhibitors of the Small Multidrug Resistance Protein from Pseudomonas aeruginosa

Abstract: Bacteria have acquired multiple mechanisms to evade the lethal effects of current therapeutics, hindering treatment of bacterial infections, such as those caused by the pathogen Pseudomonas aeruginosa, which is responsible for nosocomial and cystic fibrosis lung infections. One resistance mechanism involves membrane-embedded multidrug efflux pumps that can effectively extrude an array of substrates, including common antibiotics, dyes, and biocides. Among these is a small multidrug resistance (SMR) efflux prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…These small peptides can function as novel bioactive molecules that regulate several biological processes 42 44 . Small peptides can act as a hormone 45 , 46 , biocide 47 , and as an anti-cancer therapeutic agent 48 , 49 . The presence of these small peptides and their activity can have a significant impact on the physiology of an organism.…”
Section: Resultsmentioning
confidence: 99%
“…These small peptides can function as novel bioactive molecules that regulate several biological processes 42 44 . Small peptides can act as a hormone 45 , 46 , biocide 47 , and as an anti-cancer therapeutic agent 48 , 49 . The presence of these small peptides and their activity can have a significant impact on the physiology of an organism.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that niosome‐encapsulated tobramycin could reduce the EtBr MIC value by two to four times which is indicating the efflux pump inhibitory of niosome encapsulated tobramycin. Efflux pump systems in P. aeruginosa strains expel antimicrobial agents out the cells, contribute to the intrinsic resistance of bacteria 57,58 . Moreover, biofilm formation reduces the efficacy of antimicrobial agents and several studies showed the relationship between biofilm formation and antibiotic resistance 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biofilm formation reduces the efficacy of antimicrobial agents and several studies showed the relationship between biofilm formation and antibiotic resistance 59 . Efflux pump inhibition is a valuable approach to overcome antibiotic resistance 57 . Recently, most of researchers is focused on the development of efflux inhibitors especially RND efflux pump inhibitors 57,60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MdtIJ, a heterodimer classified as EmrE-like via sequence, was shown to transport spermidine, a metabolite, rather than acting as a multidrug transporter (20,21). This raises the question of how much functional variation exists within each subfamily, and how well functional phenotypes correlate with bioinformatic classifications, since experimental assessment of transport or drug resistance phenotypes has only been performed for a relatively small number SMR homologs and limited number of substrates (1,9,15,(22)(23)(24)(25)(26). Here we experimentally confirm the EmrE-like classification of two SMR homologs from bacterial pathogens, SMRSa from Staphylococcus aureus and SMRFt from Francisella tularensis by comparing the results of resistance assays of these SMRs to EmrE.…”
mentioning
confidence: 99%